IMPORTANCE OF LOCATION AND EXTERIOR OF CITY HOTELS AS ELEMENTS OF GUEST SATISFACTION - Tepavčević, Jelena D; Blešić, Ivana V; Bradić, Milan D; Ivkov, Milan Č; Stefanović, Vidoje D (Arhitektura i urbanizam, 2016)
Business practices and attitudes of tourists show that hospitality represents the primary factor in the development of urban tourism. It is considered that, besides the exclusive appearance, there is no business success for hotel properties without a proper location. It is known that a typical tourist would like to be close enough to tourist attractions, to be able to reach them on foot. This paper deals with the importance of location and exterior of urban hotels on guests decision on the selection and overall satisfaction with hotel products. The survey was conducted in the hotels two largest urban centers in Serbia (Belgrade and Novi Sad). The aim of the research is an insight into the real impact of location and exterior when assessing the guest satisfaction. Descriptive statistical analysis, t-test and regression analysis were used for statistical data processing.